PEMELIHARAAN KOREKTIF MESIN CETAK OFFSET 4 WARNA PADA CV. ARIES ANUGRAH KARYA UTAMA - Luthfi Irdiansyah; Eka Ludiya (Jurnal Administrasi Bisnis, 2022)
This study aims to analyze the corrective maintenance of the 4 Color Offset Printing machine at CV.Aries Anugrah Karya Utama. Another goal is to find out to what extent the corrective maintenance of the 4 Color Offset Printing machine has been running effectively and efficiently. The method used in this research is descriptive with a qualitative approach, using purposive sampling technique. The technique of collecting data by doing observation, interview and documentation, to test the validity and reliability by using triangulation of sources, triangulation of techniques and time triangulation. The results of this study indicate that the availability of corrective maintenance has not reached the predetermined target which has a percentage of less than 90%. In corrective maintenance preparations it was found that the preparation of spare parts was not optimal due to incomplete inventory, furthermore the documentation and corrective maintenance procedures were not optimal. In this case there is still much that needs to be improved in the corrective maintenance of the 4 color offset printing machine on CV.Aries Anugrah Karya Utama , such as corrective maintenance preparation needs to be improved, corrective maintenance procedures need to be designed properly and corrective maintenance documentation needs to be better managed.